Behaviorism and Foreign Language Teaching Methodology - Budiman, Asep (Institut Agama Islam Negeri (IAIN) Curup, 2017)
ABSTRACT This paper aims at exploring in details about one of the left language learning theoriesnamely Behaviorism. Behaviorism, as how it is today, is gradually left behind since there are many new theories of language learning. Regarding this issue, it is very important to ensure that actually Behaviorism is still useful in certain teaching and learning activities in the classroom. This review investigates behaviorism methodology having advantages in learning a language in the classroom. This review also observes the critics of behaviorism and its weaknesses in a learning environment. This inquiry concentrates on the view point of B.F. Skinner, one of the most outspoken behaviorism psychologist and his experimentations about animals. The notion of antimentalism of behaviorism also discussed in the process. Keywords: Behaviorism Theory, Foreign Language, Teaching Methodology